2018
DOI: 10.4236/ajmb.2018.84018
|View full text |Cite
|
Sign up to set email alerts
|

Ca<sup>2+</sup>-Induced Conformational Change of Troponin C from the Japanese Pearl Oyster, <i>Pinctada fucata</i>

Abstract: Troponin is a thin filament-associated regulator of vertebrate striated muscle contraction. Troponin changes its structure upon Ca 2+ binding to troponin C, one of the subunits of troponin, allowing myosin to interact with actin. We recently elucidated the molecular characteristics of the Japanese pearl oyster Pinctada fucata troponin C (Pifuc-TnC), revealing the possibilities that Pifuc-TnC and vertebrate muscle TnC play dissimilar roles in muscle contraction. Pifuc-TnC has four EF-hand motifs, but, unlike ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…We recently showed that TnC, a subunit of Tn, might participate in the regulation of phasic muscle by virtue of its molecular characterization [5] [19]. In this study, DSC analysis clearly revealed that the types of TM isolated from phasic and catch muscles are different ( Figure 6), raising the possibility that Tn might interact with Pifuc-TM-1.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We recently showed that TnC, a subunit of Tn, might participate in the regulation of phasic muscle by virtue of its molecular characterization [5] [19]. In this study, DSC analysis clearly revealed that the types of TM isolated from phasic and catch muscles are different ( Figure 6), raising the possibility that Tn might interact with Pifuc-TM-1.…”
Section: Discussionmentioning
confidence: 56%
“…It was reported in a scallop striated muscle study that the movement of TM was induced by the Ca 2+ concentration, as it is in vertebrates [6]. Pifuc-TM-2 might be involved in phasic muscle regulation in collaboration with Tn, which is expressed mainly in phasic muscle [5] [19].…”
Section: Discussionmentioning
confidence: 90%
“…Our studies have focused on the adductor muscle Tn subunits to investigate the molecular mechanism of thin filament-linked regulation of molluscan muscle contraction. To this end, we recently characterized P. fucata TnC (Pifuc-TnC) [12] [13]. Pifuc-TnC has four EF-hand motifs, sites I-IV, and, like other molluscan TnCs [14] [15] [16], only site IV is able to bind Ca 2+ [12].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we recently characterized P. fucata TnC (Pifuc-TnC) [12] [13]. Pifuc-TnC has four EF-hand motifs, sites I-IV, and, like other molluscan TnCs [14] [15] [16], only site IV is able to bind Ca 2+ [12]. A conformational change is induced in Pifuc-TnC upon Ca 2+ -binding [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation